Back pain – analysis of risk factors and the frequency of ailment occurrences - Szymon Pasiut; Angelika Osińska (Rehabilitacja Medyczna, 2016)
The aim of the study was to analyze the risk factors of back pain in M.A. students. The study involved 150 physical therapy students from the University School of Physical Education (AWF) in Krakow and 100 applied information technology (IT) students from the Cracow University of Technology. The study group was determined on the basis of dean’s lists and quota sampling. The study was conducted using a proprietary questionnaire. The results showed that the level of knowledge on prevention of back pain in physical therapy students is greater than in science students. Physiotherapy students experience back pain more often than IT students. The physical activity level of physical therapy students is higher than the IT students. The type of activity may signifi cantly affect the occurrence of back pain in students. The presented results may be indicative of the significant effect of stress on the occurrence of pain among students.